Wrenching Tectonism in the Southernmost Andes and the Scotia Sea Constrained from Fault Kinematic and Seismotectonic Overviews - Sue, Christian; Ghiglione, Matias
The geodynamics of the study area includes subduction, orogen dynamics, and major transcurrent tectonics at a complex transform margin in the southern ocean. We present a synthesis of the fault system associated to major fault zones in the Fuegian Andes and the Scotia Sea and review the available kinematic databases from microtectonic measurements. Our synthesis of six independent fault kinematic studies is coherent with a very consistent shortening direction-oriented NE–SW in the Southernmost Andes. The stability of the stress pattern and orientation of the shortening axes on a more regional scale involving the Scotia Sea indicate a steady E–W to NNE–SSW σ1/shortening direction since middle Eocene times. This observations reflect that the global left-lateral motion between Antarctica–Scotia–South America plates circuit is the main driving force for the entire area and in particular for the Southernmost Andes, over the last ~45 Ma. Both the observed short-term geodetic and the long-term geological slip rates of the Magallanes–Fagnano fault system from Tierra del Fuego are moderate (~5 mm/year), and the expected time span between major M8 earthquakes would be around 10 kyr. Yet the time between the two most recent large earthquakes was about 70 years. Such a great discrepancy suggests a complex mechanics on the Magallanes–Fagnano fault system, leading to complex recurrence time history for the characteristic earthquake (M ≥ 7). Fil: Sue, Christian. Universite de Bourgogne; Francia Fil: Ghiglione, Matias. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina